From a sports mega-event to a regional mega-project: the Sochi winter Olympics and the return of geography in state development priorities. Issue 2 (3rd April 2017) - Golubchikov, Oleg
ABSTRACT: This article explores the relationships between sport, space and state in the 2014 Sochi Winter Olympics. While the extant literature has predominantly attributed the Russian government's motives behind hosting the Olympics to showcasing Putin's Russia, this article provides a more nuanced account of the Sochi project in light of its entanglements with regional development and its implications for Russia's spatial governance. It argues that Sochi has been an important experimental space for the federal state in its reconstitution and re-territorialisation of the institutions of economic development. The Sochi project signposts a dual process: the return of regional policy to the state's priorities and a (selective) return of the federal state to urban development. Whilst not without controversies and inconsistencies, this practice signifies a re-establishment of strategies seeking a more polycentric economic development, including through supporting places on Russia's less developed peripheries. The article also presents insights into the practical operations of the Sochi project and its legacies, including most recent data on the disbursement of its budget.